Implementation path and reference framework for Industrial Internet Platform (IIP) in product service system using industrial practice investigation method. (January 2022) - Zhang, Xianyu; Ming, Xinguo
Highlights: A reference framework for IIP in product service system is proposed. Subsystems for IIP in product service system are proposed. An industrial implementation path for IIP in PSS for IIP is given. It can enhance the core value of enterprises and increase benefits. It has a certain reference value for industry and government. Abstract: With the development of intelligent sensing, edge computing, fog computing, cloud computing, parallel computing, smart grid, big data, block chain, 5G, cyber-physical systems, digital twins, machine learning and other technologies, the industrial internet has undergone control network stage, sensor network stage, internet stage, Internet of Things (IoT) stage, Industrial Internet of Things (IIoT) stage, and Industrial Internet (II) stage, etc. In the existing research, scholars focus on a local dot, such as: technology, function, elements and application based on industrial internet. However, there is a lack of an overall framework to study the top-level planning of Industrial Internet Platform (IIP) from a systematic perspective. On the other hand, there are few studies on the detailed path and steps for implementing IIP in a specific enterprise in a specific industry. The objective of this paper is to study a reference framework and industrial implementation path for IIP in product service system using industrial practice investigation method, which meets the needs of industry on the basis of existing theory and industrial practice, and to provide reference for government and industry planning, design, implementation and promotion of IIP. In addition, the proposed reference framework and industrial implementation for IIP in product service system can enhance the core value of the enterprise and increase benefits.